Self-regulated Learning Questionnaire: Differential Item Functioning (DIF) and Calibration using Rasch Model Analysis - Mumpuni, Kistantia Elok; Begimbetova, Guldana Atymtaevna; Retnawati, Heri (Jurnal VARIDIKA, 2023)
Questionnaires are commonly utilized on educational research. However, studies on Differential Item Functioning (DIF) and calibration using Rasch Models are still limited. Therefore, a Self-regulated Learning questionnaire was developed which aims to determine the ability of students to regulate themselves to achieve learning goals. The instrument consists of twelve items. The involved participants were 300 students who enrolled in first-year to fourth-year. Data were analyzed using Racsh Model Analysis with Winsteps 4.5.2 software. As a result, there are four items that were not fit, so that, therefore should be eliminated or revised. The DIF analysis found that gender bias was unidentified, but long-study bias was detected for items number one and six. The reliability value of the item is categorized as very good (0.99), which indicates that the instrument has sufficient consistency/reliability. While, the function curve showed that the items on the self-regulated learning questionnaire produce optimal information in individuals with moderate (θ) ability. Overall, self-regulated learning questionnaires have to be revised then tested on different sample groups. In addition, longitudinal and cross-sectional research is necessary to determine the level of self-regulated learning of students more comprehensively.